2001
DOI: 10.1046/j.1365-2559.2001.01229.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA topoisomerase IIα expression correlates with cell proliferation but not with recurrence in intracranial meningiomas

Abstract: TopoIIalpha expression may be useful as a novel proliferation marker in meningiomas, presenting several advantages over the markers currently in use, notably providing a better estimate of the number of cycling cells and a more uniform nuclear staining pattern. However, it fails to discriminate between benign and atypical neoplasms and does not provide prognostic information beyond that obtained by Ki67.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…However, heterogenicity of cell populations and features secondary to technical manipulation which may mask the mitotic figures, 7,46 render proliferation markers for quantitative assessment of the biological behavior of meningiomas necessary. [2][3][4][5][6][7][8][9][10] Numerous studies have shown that immunohistochemistry of the nonhistone nuclear protein Ki-67, expressed in the G 1 , S, G 2 , and M phases of the cell cycle, may be the simplest and most reliable means of estimating growth fractions in various brain tumors including meningiomas. [2][3][4][5][6][7][8][47][48][49] The monoclonal MIB-1 antibody detects recombinant Ki-67 antigen, 11,12 but unlike previ- ously available Ki-67 antibodies, MIB-1 can be used on formalin fixed, paraffin-embedded tissue as it detects a fixation and embedding resistant epitope on the Ki-67 antigen in sections previously microwaved in a citrate buffer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, heterogenicity of cell populations and features secondary to technical manipulation which may mask the mitotic figures, 7,46 render proliferation markers for quantitative assessment of the biological behavior of meningiomas necessary. [2][3][4][5][6][7][8][9][10] Numerous studies have shown that immunohistochemistry of the nonhistone nuclear protein Ki-67, expressed in the G 1 , S, G 2 , and M phases of the cell cycle, may be the simplest and most reliable means of estimating growth fractions in various brain tumors including meningiomas. [2][3][4][5][6][7][8][47][48][49] The monoclonal MIB-1 antibody detects recombinant Ki-67 antigen, 11,12 but unlike previ- ously available Ki-67 antibodies, MIB-1 can be used on formalin fixed, paraffin-embedded tissue as it detects a fixation and embedding resistant epitope on the Ki-67 antigen in sections previously microwaved in a citrate buffer.…”
Section: Discussionmentioning
confidence: 99%
“…As histologic analysis has limited value in predicting the neoplastic behavior of meningiomas, human studies have evaluated proliferation markers such as Ki-67, [2][3][4][5][6][7][8] proliferating cell nuclear antigen (PCNA), 8,9 and mitosin 10 in addition to the mitotic index. 4,6,7,9,10 Ki-67 is a marker of cell proliferation that is expressed in all active phases of the cell cycle. 11 The monoclonal antibody MIB-1 labels the Ki-67 antigen and proliferation rate can be defined by the MIB-1 Labeling Index (LI), which is calculated from the percentage of positive staining cells.…”
mentioning
confidence: 99%
“…In the present study, we investigated caspase-3 immunoreactivity in a series of intracranial, totally resected meningiomas, as a continuum of previous studies of our group, aiming to determine prognosticators of meningioma recurrence [5,[22][23][24]. Despite the importance of apoptosis in the development of central and peripheral nervous system, there are rather few reports concerning the magnitude of cell deletion in meningiomas [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Ki-67 has been claimed to be the best indicator of prognosis [3][4][5][6][7][8][9][10][11][12]. In addition to Ki-67, some novel proliferation markers such as mitosin and 2 clones of topoisomerase IIα (Ki S1 and 3F6) as well as minichromosome maintenance-2 protein have been reported to be useful [13][14][15][16]. Another marker related to proliferation is telomerase, a telomerase synthesing protein that contributes to continuous proliferation and immortality, whereas the exhaustion of telomeric repeats triggers apoptosis [17,18].…”
Section: Introductionmentioning
confidence: 99%